Laporan Keuangan Umkm Katering Mbok Dade dan Pengaruhnya Pada Akses Kredit Perbankan Era Pandemi Covid-19 - Pratomo Cahyo Kurniawan; Singgih Setiawan; Nafilah . (ECONBANK: Journal of Economics and Banking, 2021)
This study aims to determine the effect of MSME financial reports on access to credit that can be received by MSME entrepreneurs in the Covid 19 pandemic. This study uses primary data obtained from direct observations with catering owners Mbok Dade. The analysis technique used is descriptive qualitative. The results of the study indicate that the MSME Financial Statements can be one of the supporting factors in obtaining access to bank credit. Other factors can be in the form of profiles ofprospective customers and credit guarantees.